SCAFFOLD BHA/GELATIN DENGAN PELAPIS PVA UNTUK APLIKASI IMPLAN - Alva Edy Tontowi, MK Herliansyah, dan Punto Dewo (Universitas Gadjah Mada, 2013)
Hard tissue defect, particularly at the bone structure, is a common problem in Indonesia causing improper function. About 60% of it is caused by defects that occur since birth, and the rest is caused by other factors, such as accidents. To treat these problems, medical doctor usually carry out transplantation or implantation. Implantation is done by filling the bone cavity with biomaterial made from Ca/P-based material, such as hydroxyapatite (HA). In the form of powder, pure HA is difficult to be formed into a certain shape and geometry since this material is brittle and has a high melting point (1400 oc), which is impossible to reach in a surgery environment. Additionally, in the form of macro-porous blocks, they are very weak and easy to break, far from the requirements. In order to form pure HA at room temperature and still fulfill the required strength, other biocompatible materials are needed. In this work, HA, gelatin and PVA were used to form samples. The HA was derived from bovine bone, bioactivity and oteoconductivity. Gelatin was used as a matrix of the composite, whilst Polyvynil Alchohol (PVA) acted as a coating. The HA was derived by calcination of bovine chips at 900 oC for 2 hours, while the gelatin (G) and PVA were supplied by commercial purchase. The ratio of [G/bHA] to distilled water (H2O) was 30%, 40% dan 50% w/v. PVA 0.2% w/w coating was done by dipping the block in liquid nitrogen (N2). Tests were performed by DTS and microstructure analysis was carried out by SEM. The results show that sample with [G/bHA] of 50% w/v gave DTS of 6.219 MPa. This tensile strength matched the strength of human bone from a 62 year old person. ????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????